Comparison of depression between kidney transplant recipients from live donors with cadavers in hospitals of Mashhad University of Medical Sciences - Parsaei Mehr, zahra; Moshtagh Eshgh, zahra; Hami, maryam; Fesharaki, mohamad (Advances in Nursing & Midwifery, 2014)
Abstract Background & aim: Kidney transplant surgery may impact various aspects of the life and results in individual and psychological problems. Receiving a kidney from a cadaver donor is associated with beliefs related to death of donor and with recipient’s survival. The aim of this study was to compare the rate of depression in patients receiving kidney from living donors with cadaveric donor kidney transplant ,patients that were referred to nephrology clinics in hospitals of Mashhad University of Medical Sciences in 2010. Materials & methods: A descriptive – comparative design was used. The sample of the study consisted of 60 patients receiving kidney from living donors and 60 cadaveric kidney transplantation attended to nephrology clinics in hospitals of Mashhad University of Medical Sciences. Data were collected by a demographic questionnaire and Beck depression Inventory. The reliability of this test was evaluated with test-retest and Pearson correlation test was 0. 95. Data were analyzed with SPSS software (version 13). Finding: Depression scores in living kidney transplantation group were 11. 6±5. 7 , and in the cadaveric group was 16. 4±9. 4. Independent t-test showed a significant difference between two groups scores of depression (P<0. 005). Conclusion: The results showed a higher depression scores in kidney transplantation from cadaveric donors. Therefore it is recommended that efforts to detect and treat depression be included in the care of transplant patients before and after the surgery.. Key words: Kidney transplant, Cadaver, Live donors, Depression REFERENCES Akman B et al (2004) Depression levels before and after renal transplantation. Transplantation Proceedings. 36(1) 111-113 Anvar-Abnavi M, Bazargani Z) 2010(Prevalence of anxiety and depression in Iranian kidney transplant recipients. Neurosciences (Riyadh). 15(4) 254-7. Arapaslan B, et al(2004) Cross-sectional assessment of psychiatric disorders in renal transplantation patients in Turkey: A preliminary study. Transplantation Proceedings. 36(5) 1419_1421. Baines LS, et al (2002) Emotional issues after kidney transplantation: A prospective psychotherapeutic study. Clinical Transplantation, 16(6)455-460 Bakhshaei N & et al (2003) [Relationship between perceived social support and life stressful events with depression]. Andeeshe va Raftar. 9(2)49-55(Persian). Corruble E et al (2010) Progressive increase of anxiety and depression in patients waiting for a kidney t / 45 م ی ی ransplantation, Behavioral Medicine. 36(1) 32-36 . Di Martini A et al (2008) Psychiatric aspect of organ transplantation in critical care. Critical Care Clinics. 24(4) 949-969 . Dublse F et al (2008) Depression disorder in renal transplantation: An analysis of Medicare cliams, American Journal of kidney Disease. 51(5) 713-874 Fortinash K,Holoday Worret P(2008). Psychiatric Mental Health Nursing. 4th ed. Mosby,Elsevier. Ghafari A (2008) “Tehran two-day seminar on kidney transplant “, Special Medical Engineering Magazine, No. 92, December 87, p. 36. [Persian]. Heisler J “Coping After A Life Saving Organ Transplant” February 14, 2009, [on line],www. About. com. [3 septamber 2010]. Karaminia R, et al (2007) Anxiety and depression:A comparison between renal transplant recipients and hemodialysis patients. Transplantation proceeding, 39(6)1082-1084. Masoudi Alavi N, Sharifi Kh, Ali Akbarzadeh Z (2008) [Depression and anxiety in patients undergoing renal replacement therapy in the years 1385 to 1386 in Kashan]. Faiz Journal. 12(4) 46-51. (Persian). Molahadi M,Tayebi A, Ebadi A, Daneshmandi M (2010)[ A Comparative study of anxiety, depression and stress in hemodialysis and kidney transplantation patients]. Iranian Journal of Critical Care Nursing (IJCCN) 2(4) 9-10. (Persian). Nickel R, Wunsch A, Egleut , et al (2002) The relevance of anxiety , depression , and coping after liver transplantation. Liver Transplantation. 8(1)63-71. Novak M (2010),»Depressive symptoms and mortality in patients after kidney transplantation ”, April 21,2010, [on line], < http://www. psychosomaticmedicine. org/misc/terms. shtml>. [January 24, 2010] Pascazio L et al, (2010) Anxiety, depression and emotional profile in renal transplant recipients and healthy subjects: A comparative study. Transplantation Proceedings. 42(9) 3586-3590 Pawar A et al «Cognitive and emotional effects of renal transplantation»,1 January 2006, [on line] < http://www. highbeam. com/ /doc/1G1-162575248. html>. [3 Apr 2010]. Perez S-G et al (2008) Influence of the psychological state of relatives on the quality of life ofpatients at 1 year after transplantation. Transplantation Proceeding. 40(9)3109-11. Rezaei R et al (2009)[ Comparison of body image in hemodialysis patients with kidney transplant patients]. payesh Quarterly . 8(3) 279-287. (Persian). Sayin A et al (2007) Quality of life in hemodialysis, peritoneal dialysis, and transplantation patients. Transplantation Proceeding. 39(10) 3047-3053. Shah VS, et at (2006) Qualify of life and psychosocial factors in renal transplant Recipients. Transplantation Proceedings. 38(5) 1283-1285. Sugawara H et al (2008) Paradoxical depression in renal transplant recipient. Transplantation Proceeding. 40(10) 3448-3450. Szeifert L et al(2010) Symptoms of depression in kidney transplantations: A cross-sectional study. American Journal of Kidney Diseases (AJKD). 55(1)132-140. Toimamueang U et al (2003) Stress and coping strategies among renal transplant candidates in a stress and coping strategies among renal transplant candidates in a Thai medical center. Transplant Proceedings. 35(1) 292-3. Virzi A, et al (2007) Depression and quality of life in living related renal transplantation. Transplantation Proceedings. 39(6) 1791-1793. Weng LC, et al (2006) Effects of self-efficacy, self-care behaviors on depressive symptom of Taiwanese kidney transplant recipients. Journal of Clinical Nursing, 17(13) 1786-1794.